Boron uptake and translocation in some cotton cultivars - Bogiani, Julio C.; Sampaio, Thalita F. [UNESP]; Abreu-Junior, Cassio H.; Rosolem, Ciro Antonio [UNESP] (Springer, 2014)
Boron (B) is the most deficient micronutrient in cotton (Gossypium hirsutum L.). It is generally accepted that B is immobile in cotton phloem, but some cultivars could remobilize the nutrient. In order to further understand B uptake and mobility in various cotton cultivars two experiments were conducted.In experiment-1, cotton cultivars were grown in B-10 enriched or natural abundance nutrient solutions for 4 weeks and transferred to nutrient solutions ranging from deficient to sufficient in B. In experiment-2 B-10 enriched boric acid was applied to cotton leaves and B mobilization was determined.In deficient plants, B previously supplied to roots was remobilized from older to younger plant tissues, but the amount was insufficient to maintain growth. Boron deficiency symptoms appeared and progressed with time. Boron applied to leaves was taken up and remobilized within 24 h. Boron mobilization was higher to plant parts above the treated region.Boron uptake and mobilization was similar among cotton cultivars. Boron applied to cotton leaves shows a preferential translocation to younger tissues. Foliar sprays of B to cotton may be used to cope with a temporary deficiency, but to achieve full growth and development B must be available to cotton throughout the plant cycle.
Keywords: Cotton; Micronutrient; Boron; Translocation; Remobilization